Soundin'Place - Promovendo a criação de narrativas sonoras em contexto pedagógico - Pedro Henrique Rodrigues Luís (2020)
This dissertation seeks to understand how musical technology can promote the development of critical listening and sound narrative skills. Its use would bem ade in a pedagogical context. The methodology used went through a literature review, followed by the creation of the application and its heuristic evaluation. The analysis of the heuristic evaluation allows a better perception of how improvements can be made. The user controls a set of parameters, adjusting the behaviour of each sound object, thus creating his own sound narrative. As its purpose is to use it in a pedagogical context, sessions were also created so that different theoretical foundations could be transmitted to students. By exploring sound objects and different ways of controlling their behaviour, it is proposed that there is a promotion of cognitive development, as a dynamic classroom activity.